PENGARUH RISIKO AUDIT, UKURAN AUDITOR, DAN JUMLAH KEY AUDIT MATTERS (KAM) TERHADAP BIAYA AUDIT DENGAN EFEKTIVITAS KOMITE AUDIT SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan non-Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2024) - Patricia Edith Yolanda Sitanggang; Dwi Ratmono (Diponegoro Journal of Accounting, 2026)
This study aims to examine the effect of audit risk, audit size, and the number of Key Audit Matters on audit fees, as well as the moderating role of audit committee effectiveness in those relationships. The research objects are non-financial companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2024 period. Samples were selected using purposive sampling based on specific criteria, resulting in 1.996 observations from 499 companies. The analytical method used in this study is Partial Least Square Structural Equation Modeling (PLS-SEM) using WarpPLS 8.0 software.The results show that the audit risk and auditor size have a significant positive effect on audit fees, whereas the number of KAMs was not found to have a significant effect on audit fees. Audit committee effectiveness strengthens the effect of the audit risk on audit fees. Meanwhile, audit committee effectiveness weakens the effect of the number of KAMs on audit fees, indicating that an effective audit committee acts as a substitute for external monitoring, thereby reducing reliance on external auditors in handling each KAM item.